Polyamine metabolism and anti-tumor immunity - Wu, Jing-Yi; Zeng, Yan; You, Yu-Yang; Chen, Qi-Yue (Frontiers in Immunology, 2025)
Growing attention has been directed toward the critical role of polyamines in the tumor microenvironment and immune regulation. Polyamines, primarily comprising putrescine, spermidine, and spermine, are tightly regulated through coordinated biosynthesis, catabolism, and transport, with distinct metabolic patterns between normal and cancerous tissues. Emerging evidence highlights the pivotal role of polyamine metabolism in tumor initiation, progression, and metastasis. This review aims to elucidate the differences in polyamine biosynthesis, transport, and catabolism between normal and cancerous tissues, as well as the associated alterations in tumor epigenetic modifications and resistance to immune checkpoint blockade driven by polyamine metabolism. Polyamine metabolism influences both tumor cells and the tumor microenvironment by modulating immune cell phenotypes—shifting them towards either tumor suppression or immune evasion within the tumor immune microenvironment. Additionally, polyamine metabolism impacts immunotherapy through its regulation of key enzymes. This review also explores potential therapeutic targets and summarizes the roles of polyamine inhibitors in combination with immunotherapy for cancer treatment, offering a novel perspective on therapeutic strategies.